Boosting Language Learners’ Motivation Through Teacher Praise and Feedback - Syafitri, Dewi; Khairunnisa, Nabilah (STKIP PGRI Lubuklinggau, 2025)
Motivation is an important part of language learning because it affects how much effort students give, how they feel about learning, and how long they stay committed. When students are motivated, they are more likely to enjoy learning and try harder to improve their skills. This paper explores the role of teacher praise and feedback in helping students stay motivated in English as a foreign language (EFL) classrooms. Praise helps students feel appreciated and more confident, while feedback gives them direction and helps them improve. Many studies show that praise and feedback together give better results than when used separately. They support both academic improvement and emotional well-being. This review suggests that using both strategies is a helpful way to create a positive classroom and support students in becoming more independent and motivated learners.